Fabrication and Optical Properties of Silicon Nanowires Arrays by Electroless Ag-catalyzed Etching - Tang, Jie; Shi, Jianwei; Zhou, Lili; Ma, Zhongquan (Nano-Micro Letters, 2011)
In order to realize ultralow surface reflectance and broadband antireflection effects which common pyramidal textures and antireflection coatings can’t achieve in photovoltaic industry, we used low-cost and easy-made Ag-catalyzed etching techniques to synthesize silicon nanowires (SiNWs) arrays on the substrate of single-crystalline silicon. The dense vertically-aligned Si NWs arrays are fabricated by local oxidation and selective dissolution of Si in etching solution containing Ag catalyst. The Si NWs arrays with 3 μm in depth make reflectance reduce to less than 3% in the range of 400 to 1000 nm while reflectance gradually reached the optimum value with the increasing of etching time. The antireflection of Si NWs arrays are based on index-graded mechanism: Si NWs arrays on a subwavelength scale strongly scatter incident light and have graded refractive index that enhance the incidence of light in usable wavelength range. However, surface recombination of Si NWs arrays are deteriorated due to numerous dangling bonds and residual Ag particles.